2021
DOI: 10.17759/cpse.2021100108
|View full text |Cite
|
Sign up to set email alerts
|

Aggression and Belief in a Just World Among Adolescents from Belarus and Ukraine: A Comparative Analysis

Abstract: In connection with the spread of a culture of violence in modern society the problem of aggressive behavior of adolescents takes on new impetus. For a comprehensive consideration of this problem, one should take into account not only the intrapersonal and interpersonal aspects of the personality relations system, but also its relations with the world, which can be expressed in the two forms of the belief in a just world — general belief in a just world and personal belief in a just world. 70 Belarusian and 109… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…We expected that the more people believed in a just world the more they believed people became rich through their own efforts and abilities. A recent study showed that a strong BJW was associated with reduced aggression among juveniles (Larionov et al, 2021) with ramifications for how perceptions of skewed economic distributions may translate into social dissatisfaction. Thus, Hypothesis 1: Beliefs in a just world (BJW) is positively related to beliefs in agentic paths to wealth and negatively related to inheritance.…”
Section: Arnulf Robinson and Furnhammentioning
confidence: 99%
“…We expected that the more people believed in a just world the more they believed people became rich through their own efforts and abilities. A recent study showed that a strong BJW was associated with reduced aggression among juveniles (Larionov et al, 2021) with ramifications for how perceptions of skewed economic distributions may translate into social dissatisfaction. Thus, Hypothesis 1: Beliefs in a just world (BJW) is positively related to beliefs in agentic paths to wealth and negatively related to inheritance.…”
Section: Arnulf Robinson and Furnhammentioning
confidence: 99%